2022
DOI: 10.1007/s40620-022-01494-8
|View full text |Cite|
|
Sign up to set email alerts
|

Clinical features suggesting renal hypouricemia as the cause of acute kidney injury: a case report and review of the literature

Abstract: Hypouricemia is defined as a level of serum uric acid below 2 mg/dl. Renal hypouricemia is related to genetic defects of the uric acid tubular transporters urate transporter 1 and glucose transporter 9. Patients with renal hypouricemia can be completely asymptomatic or can develop uric acid kidney stones or acute kidney injury, particularly after exercise. Renal hypouricemia is especially challenging to diagnose in patients with acute kidney injury, due to the nonspecific clinical, hematochemical and histologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Accordingly, individuals with hypouricemia may be susceptible to the organic free radicals constantly generated by the activities of daily living. Therefore, hypouricemia increases oxidative stress and induces post-exercise renal artery spasm, resulting in the loss of kidney function [33,34]. However, in the present study, in which KFD was defined as the decrease in eGFR to below 60 mL/min/1.73 m 2 during the study period, the group with the lowest SUA showed the lowest risk of KFD (Figure 1B).…”
Section: Discussionmentioning
confidence: 48%
“…Accordingly, individuals with hypouricemia may be susceptible to the organic free radicals constantly generated by the activities of daily living. Therefore, hypouricemia increases oxidative stress and induces post-exercise renal artery spasm, resulting in the loss of kidney function [33,34]. However, in the present study, in which KFD was defined as the decrease in eGFR to below 60 mL/min/1.73 m 2 during the study period, the group with the lowest SUA showed the lowest risk of KFD (Figure 1B).…”
Section: Discussionmentioning
confidence: 48%
“…Renal hypouricemia is a rare inherited disorder characterized by impaired urate reabsorption in the proximal tubule resulting in low urate levels (1). Uric acid kidney stone or acute kidney injury may develop, especially after exercise (2). To date, there have been few reports of hypouricemia associated with IgA nephropathy.…”
Section: Introductionmentioning
confidence: 99%
“…However, intracellular uric acid has been linked to elevated inflammation and heightened oxidative stress ( 4 ). Extensive research has identified high serum uric acid levels as an independent risk factor for various chronic kidney and joint disorders ( 5 ), including gout ( 6 ), chronic arthritis ( 7 ), joint deformity, and uric acid kidney stones ( 8 ), as well as chronic metabolic diseases such as hypertension ( 9 ), diabetes ( 10 ), and metabolic syndrome, along with cardiovascular disease ( 11 ).…”
Section: Introductionmentioning
confidence: 99%